Spatial Structure of Low Salinity Submesoscale Features and Their Interactions With a Coastal Current - Jhugroo, Khushboo; O'Callaghan, Joanne; Stevens, Craig L.; Macdonald, Helen S.; Elliott, Fiona; Hadfield, Mark Gregory (Frontiers in Marine Science, 2020)
Submesoscale features, characterised by a low salinity layer originating from river discharges, enhance water column stability in a New Zealand shelf sea - the Greater Cook Strait. Using a combination of data from multiple ocean glider surveys and regional modelling, we show that low salinity submesoscale features (LSMFs) can cause increased stratification on the order of 10^-4. Modelled oceanographic conditions compared well to observations, especially in austral spring. Stably stratified LSMFs can replace the previously well mixed layer in the water column up to a distance of 100 km offshore before getting entrained by the regional barotropic current in Greater Cook Strait. LSMFs observed from glider surveys and reproduced from modelled results generate strong vertical and horizontal salinity differences of ~0.45 psu. These salinity differences define density fronts and stratification in the upper ~30 m. Temperature differences of up to ~1.4°C associated with LSMFs were not large enough to entirely cancel the density effect of salinity. The offshore advection reach of LSMFs is partly constrained by the variability of the barotropic d'Urville Current. Its presence and strong winds inhibit the propagation of LSMFs offshore in Greater Cook Strait, leaving the water column unstable while enhancing mixing and deepening the mixed layer depth. In contrast, moderate winds and weak current enable the propagation of LSMFs furthest offshore in Greater Cook Strait, where the water column becomes stably stratified. A stably stratified regime inhibits vertical mixing of nutrients and phytoplankton, which may lead to enhanced primary production in the region.